2017
DOI: 10.3906/vet-1604-67
|View full text |Cite
|
Sign up to set email alerts
|

Serotypes of Salmonella isolated from feces of cattle, buffalo,and camel and sensitivities to antibiotics in Turkey

Abstract: IntroductionSalmonellosis is a common bacterial enteric infection with significant economic losses for the intensive production of cattle, sheep, and poultry (1,2). Salmonella species are zoonotic and are transmitted to humans via ingestion of contaminated milk, eggs, and meat (3,4). Although Salmonella infections may occur at any age in cattle, the associated clinical symptoms are more severe in calves from the first 2 weeks to 3 months of their life (5,6).Salmonella enterica subsp. enterica may cause infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 22 publications
2
12
0
4
Order By: Relevance
“…Enteritidis (Table ). While there are similar findings by Genç (), Hadimli et al (), Rene et al (), Rizzi () reporting the presence of this serovar within their FC isolates, to the best of our knowledge, this is the first study indicating the presence of S. Enteritidis in slaughter cattle MLNs. Unusually, the other serovar isolated from FC samples was S .…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Enteritidis (Table ). While there are similar findings by Genç (), Hadimli et al (), Rene et al (), Rizzi () reporting the presence of this serovar within their FC isolates, to the best of our knowledge, this is the first study indicating the presence of S. Enteritidis in slaughter cattle MLNs. Unusually, the other serovar isolated from FC samples was S .…”
Section: Discussionsupporting
confidence: 88%
“…As an important sample type in determining NTS carriage in slaughter cattle, 1% of the FC samples in this study were determined to harbor the pathogen (Table ). In our country, Genç (), Hadimli et al (), and Küplülü () found 1.2% (3/250), 7.5% (33/437), and 14.4% (26/180) of FCs of slaughtered cattle contaminated with Salmonella , respectively. Our results are higher than 0% prevalence in 125 fecal samples reported by Bonardi, Bruini, Magnani, Cannistrà, and Brindani () from Italy; and the 0.39% prevalence of Finland in EFSA and ECDC (), but lower than the studies by Rene et al (), Ruiz et al (), and Schmidt et al () with notification rates of 5–66.4% range.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations